IMPROVING STUDENTS’ READINGAND WRITING ABILITY THROUGH IMAGE MEDIA IN GRADE 2 OF PRIMARY SCHOOL - Herdawilis Herdawilis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
The background of this research is many lower class students have not been able to read and write correctly. For this reason, the researcher tried to improve students' reading and writing skills through image media. This research was a classroom action research on grade 2 students of SDN 002 Benai with a total of 20 students. The instruments used were observation sheets and students' reading and writing tests. The results of the study in the first cycle showed that the students’ ability with average score of 67.5% with a good category then the second cycle increased to 81% which was included in the excellent category. Based on the results of the study, it can be concluded that reading and writing ability of the second grade students of SDN 002 Benai can be improved through the media of images.